Perspective: Re-defining “Pheromone” in a Mammalian Context to Encompass Seminal Fluid - Robertson, Sarah A.; Martin, Graeme B. (Frontiers in Veterinary Science, 2022)
The classical view of ‘pheromone’ – an air-borne chemical signal – is challenged by the camelids in which ovulation is triggered by ß-nerve growth factor carried in seminal plasma, effectively extending the pheromone concept to a new medium. We propose further extension of ‘pheromone’ to include a separate class of seminal fluid molecules that acts on the female reproductive tract to enhance the prospect of pregnancy. These molecules include transforming growth factor-ß, 19-OH prostaglandins, various ligands of Toll-like receptor-4, and cyclic ADP ribose hydrolase. They modulate the immune response to ‘foreign’ male-derived histocompatibility antigens on both sperm and the conceptus, determine pre-implantation embryo development, and then promote implantation by increasing uterine receptivity to the embryo. The relative abundance of these immunological molecules in seminal plasma determines the strength and quality of the immune tolerance that is generated in the female. This phenomenon has profound implications in reproductive biology because it provides a pathway, independent of the fertilising sperm, by which paternal factors can influence the likelihood of reproductive success, as well as the phenotype and health status of offspring. Moreover, the female actively participates in this exchange – information in seminal fluid is subject to ‘cryptic female choice’, a process by which females interrogate the reproductive fitness of prospective mates and invest reproductive resources accordingly. These processes participate in driving the evolution of male accessory glands, ensuring optimal female reproductive investment and maximal progeny fitness. An expanded pheromone concept will avoid a constraint in our understanding of mammalian reproductive biology.